1978
DOI: 10.1099/00222615-11-3-303
|View full text |Cite
|
Sign up to set email alerts
|

Assay of Staphylococcal  -Haemolysin with Fish Erythrocytes

Abstract: Delta-haemolysin has a much lower specific activity than the other haemolysins, and in low dilutions lyses a wide range of erythrocytes; it is usually assayed with human or horse erythrocytes and these have indicated as many as 300 haemolytic units per mg (HU per mg) in purified preparations (Heatley, 1971 ; Kreger et al., 1971). Heatley (1971) found that ,8-haemolysin was capable of interfering with the assay of 8-haemolysin when human erythrocytes were used. Lysis of bacterial protoplasts (Bernheimer et al.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Moreover, the results of attempts to elute membrane-bound toxin by ionic manipulations by Fiissle et al (1 98 1) led these authors to conclude that manipulations of the toxin which lead to loss of haemolytic activity may alter membrane-binding activity. In the present studies, binding to rabbit and horse erythrocytes was independent of temperature over the range 1-45"C, as was cell lysis induced by staphylococcal 6 lysin, a lytic agent of low specificity whose action is thought to be due to surface-active properties (Chao and Birkbeck, 1978). Cassidy and Harshman (1976a), however, found that binding to rabbit erythrocytes was temperature dependent with maximum binding at 24°C.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, the results of attempts to elute membrane-bound toxin by ionic manipulations by Fiissle et al (1 98 1) led these authors to conclude that manipulations of the toxin which lead to loss of haemolytic activity may alter membrane-binding activity. In the present studies, binding to rabbit and horse erythrocytes was independent of temperature over the range 1-45"C, as was cell lysis induced by staphylococcal 6 lysin, a lytic agent of low specificity whose action is thought to be due to surface-active properties (Chao and Birkbeck, 1978). Cassidy and Harshman (1976a), however, found that binding to rabbit erythrocytes was temperature dependent with maximum binding at 24°C.…”
Section: Discussionmentioning
confidence: 66%
“…Alpha-toxin was assayed by haemolytic titration against rabbit erythrocytes according to the method of Bernheimer and Schwartz (1963). The level of contamination of the a-toxin fraction with staphylococcal 6 lysin was estimated by titration against cod erythrocytes (Birkbeck, Chao and Arbuthnott, 1974;Chao and Birkbeck, 1978) and with staphylococcal /? lysin by titration against sheep erythrocytes (Low et al, 1974).…”
Section: Methodsmentioning
confidence: 99%
“…One liter of medium contained 4.5 g of KCI, 0.55 g of NaH2PO4, 2.5 g of glucose, t Present address: Microbiology Laboratories, School of Medicine and Dentistry, University of Rochester, Rochester, NY 14642. 2 mmol of L-isoleucine, and 20 mmol each of L-leucine, L-serine, L-phenylalanine, L-histidine, L-lysine, L-proline, L-threonine, L-aspartate, L-glutamate, L-methionine, L-asparagine, L-cysteine, L-tryptophan, L-analine, L-arginine, glycine, L-valine, and L-tyrosine. The pH was adjusted to 7.2 with 4 M NaOH, and the medium was filtered through Whatman no.…”
Section: Materla1s and Methodsmentioning
confidence: 99%
“…Delta-lysin was assayed by its hemolytic activity against a 1% (vol/vol) suspension of washed cod erythrocytes (6).…”
mentioning
confidence: 99%